Technical Summary. In: Global Warming of 1.5°C. An IPCC Special Report on the impacts of global warming of 1.5°C above pre-industrial levels and related global greenhouse gas emission pathways - Allen, Myles R.; Coninck, Heleen de; Dube, Opha P.; Hoegh-Guldberg, Ove; Jacob, Daniela (2018)
Technical summary of the IPCC Report: Global Warming of 1.5°C. An IPCC Special Report on the impacts of global warming of 1.5°C above pre-industrial levels and related global greenhouse gas emission pathways, in the context of strengthening the global response to the threat of climate change, sustainable development, and efforts to eradicate poverty.